To study the rate of HIV Sero-positivity in paediatric patients with high risk clinical profile - Singh, Tarsem; Natt, Navreet Kaur; Goel, Sneh Prabha (International Journal of Research in Medical Sciences, 2018)
Background: Understanding the magnitude and clinical profile of pediatric HIV is essential for the clinicians and policy makers. The study was aimed to determine the rate of HIV seropositivity in pediatric patients with high risk clinical profile, study the clinical presentations and the mode of transmission of HIV in children. Methods: This prospective hospital-based study to screen 244 children aged 18 months to 12 years with high risk clinical profile for HIV seropositivity was carried out for a period of 1 year. Results: Of the 244 children screened, the commonest clinical features associated with high risk profile were failure to thrive in 200 (81.97%), persistent fever in 151 (61.89%), chronic diarrhoea in 76 (31.15%), cough >1month 112 (45.90%) patients. HIV seropositivity was reported in 11/244 (4.51%) patients; with failure to thrive in 10/11 (90.90%), chronic diarrhoea in 09/11 (81.81%), seborrheic dermatitis in 2/11 (18.18%) patients followed by persistent cough, severe malnutrition, oral thrush, generalized lymphadenopathy and recurrent bacterial skin infections in 1 patient each out of 11(9.09%). Chronic diarrhoea was a significant independent clinical risk factor for predicting HIV seropositivity (Chi2 = 13.81, p<0.001, Odds ratio=11.15). The probability of HIV seropositivity increased significantly with the number of risk factors concomitantly present, with 30% seropositivity in those with four clinical risk factors (Chi2 =32.89, D. F=1, P<0.001). The parents of all seropositive children were seropositive. Conclusions: The probability of HIV infection in a child depends upon the nature and number of clinical manifestations present. All HIV positive children h HIV positive parents in this study indicating vertical transmission.